Empowered Manager - Perter Block (Wiley, 2017)
Peter Block is an original—and a wise and experienced observer of organizational life. He shares his unique and thoughtful perspective in this enlightening and provocative new edition of his classic, The Empowered Manager. Peter asks us to consider what could be possible if only we rekindled the entrepreneurial spirit and felt safe enough to speak out and take action. In this sense, empowerment becomes the foundation for leadership, and the brightest path to the future is when leadership becomes everyone's business. The Empowered Manager is at once a deeply philosophical and a highly practical book—one that needs to be read and applied by every thinking leader."=541 ## Mua